Level of human rights awareness of the PNP in Ilolio City and its effects on the discharge of their functions - Bade, Lorilyn; de leon, Roxan; Pendoy, Argelyn; Sablon, Arlyn; Superficial, Mae. (2001.)
This study seeks to determine the level of human (civil) rights awareness of the PNP members in Iloilo City and its effect on the discharge of their functions. The objectives of the study is to determine how law enforcers understand human rights, to know their level of awareness on selected civil rights and to determine whether the level of their awareness affects the discharge of their functions. The respondents are the members of Philippine National police (PNP) assigned in six (6) precincts in Iloilo City. There will be fifteen (15) respondents in every precinct. These precinct include Mandurriao, Jaro, La Paz, Molo, Arevalo and Iloilo city Proper. The descriptive method is used in this particular study. It involves description, recording, analysis, and interpretation of the present nature or processes of phenomena. Also, a questionnaire method is used in gathering data in the feelings, emotions, attitudes, and judgments of the subjects. Findings of the study reveal that almost all of the PNP in six (6) precincts are fully aware of all the human rights stated. Also, the PNP members are human rights advocate as implied in the data with regards to thier answers on the cases. Perceptions of the PNP members on human rights vary from each other. There is a contradictory in the reult of our findings with the data collected in the commission on Human Rights. The data shows that police abuses still exist despite their awareness regarding human rights.
Research Paper (Mgt 199-Management Research) -- Iloilo City : University of the Philippines in the Visayas - College of Management, [2001].